UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS MATERI KEGIATAN JUAL BELI DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) : (Penelitian Tindakan Kelas pada Siswa Kelas III SD Negeri Ancol Kecamatan Darmaraja Kabupaten Sumedang Tahun Pelajaran 2018/2019) - Avini Martini; Cep Deni Wahyudin (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2019)
This research is motivated by the lack of student activities that include attention, activity, and work together, so impressed passive learning and results in a low learning outcomes in social studies class III material purchase. This study has two formulation of the problem, namelywhether the model of Problem Based Learning (PBL) can increase the activity of social studies material trading activities and whether the model of Problem Based Learning (PBL) can improve learning outcomes IPS material trading activities of third grade students of SDN Ancol subdistrict Darmaraja, as well as the purpose of this research is, to enhance the activity and results of social studies in materials trading activities in the third grade students of SDN Ancol subdistrict Darmaraja. This study uses classroom action research (PTK) with a research design Kemmis and MC models. Taggart covering the planning, implementation, observation, and reflection. Subjects of this study third grade students of SDN Ancol subdistrict Darmaraja the Academic Year 2018/2019 of 16 people. Data collection techniques in this study is the observation techniques and engineering tests on the material buying and selling activities. After research and analysis of the data is completed, the researchers obtained data activity and learning outcomes of students has increased from the initial data to the second cycle. It is seen from the student activity on preliminary data the average amount of student activity score is 54.1, the student who gets good criteria only 3 people (18.75%), in the first cycle the average number of students activity score is 66.19 students who get good criteria to 7 students (43.75%) and the second cycle an average score of student activity is 80.75 and students who get good criteria increased to 12 (75.00%). Improved student learning activities to impact on improving student learning outcomes. This is evident from the average value of students' test results prior to implementation action planmodel of Problem Based Learning (PBL) is the average value of only 60 students by the number of students who completed only 3 people (18.75%), then after the action is taken the average value of students in the first cycle to 68.13 to the number of students who completed as many as 9 people (56.25%), and the second cycle of the average value of students has increased to 80 the number of students who completed a total of 14 people (87.50%). Abstrak Penelitian ini dilatarbelakangi oleh kurangnya aktivitas siswa yang meliputi perhatian, keaktifan, dan bekerja sama, sehingga pembelajaran terkesan pasif dan berakibat pada hasil belajar yang rendah pada mata pelajaran IPS kelas III materi jual beli. Penelitian ini memiliki dua rumusan masalah, yaitu apakah model Problem Based Learning (PBL) dapat meningkatkan aktivitas belajar IPS materi kegiatan jual beli dan apakah model Problem Based Learning (PBL) dapat meningkatkan hasil belajar IPS materi kegiatan jual beli siswa kelas III SDN Ancol Kecamatan Darmaraja, serta tujuan pada penelitian ini yaitu, untuk meningkatkan aktivitas dan hasil belajar IPS dalam materi kegiatan jual beli pada siswa kelas III SDN Ancol Kecamatan Darmaraja. Penelitian ini menggunakan metode penelitian tindakan kelas (PTK) dengan desain penelitian model Kemmis dan MC. Taggart yang meliputi tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini siswa kelas III SDN Ancol Kecamatan Darmaraja Tahun Pelajaran 2018/2019 sebanyak 16 orang. Teknik pengumpulan data dalam penelitian ini berupa teknik observasi dan teknik tes pada materi kegiatan jual beli. Setelah penelitian dan analisis data selesai dilaksanakan, peneliti memperoleh data aktivitas dan hasil belajar siswa mengalami peningkatan dari data awal sampai siklus II. Hal ini terlihat dari aktivitas siswa pada data awal rata-rata jumlah skor aktivitas siswa yaitu 54,1 , siswa yang mendapat kriteria baik hanya 3 orang (18,75%), pada siklus I rata-rata jumlah skor aktivitas siswa yaitu 66,19 siswa yang mendapat kriteria baik menjadi 7 orang siswa (43,75%) dan pada siklus II rata-rata skor aktivitas siswa yaitu 80,75 dan siswa yang mendapat kriteria baik meningkat menjadi 12 orang (75,00%). Peningkatan aktivitas belajar siswa berdampak pula pada peningkatan hasil belajar siswa. Hal ini terlihat dari nilai rata-rata hasil tes belajar siswa sebelum diterapkan tindakan perencanaan model Problem Based Learning (PBL) rata-rata nilai siswa hanya 60 dengan jumlah siswa yang tuntas hanya 3 orang (18,75%), selanjutnya setelah tindakan dilakukan nilai rata-rata siswa pada siklus I menjadi 68,13 dengan jumlah siswa yang tuntas sebanyak 9 orang (56,25%), dan pada siklus II nilai rata-rata siswa mengalami peningkatan menjadi 80 dengan jumlah siswa yang tuntas sebanyak 14 orang (87,50%). Kata kunci: Model Problem Based Learning, Aktivitas Dan Hasil Belajar